Water-Soluble and Insoluble Polymers, Nanoparticles, Nanocomposites and Hybrids With Ability to Remove Hazardous Inorganic Pollutants in Water - Rivas, Bernabé L.; Urbano, Bruno F.; Sánchez, Julio (Frontiers in Chemistry, 2018)
The polymeric materials have presented a great development in adsorption processes for the treatment of polluted waters. The aim of the current review is to present the recent developments in this field of study by examining research of systems like functional water-soluble polymers and water-soluble polymer-metal complexes coupled to ultrafiltration membranes for decontamination processes in liquid-liquid phase. Noticing that a water-soluble polymer can be turned into insoluble compounds by setting a crosslinking point, connecting the polymer chains leading to polymer resins suitable for solid-liquid extraction processes. Moreover, these crosslinked polymers can be used to develop more complex systems such as (nano)composite and hybrid adsorbents, combining the polymers with inorganic moieties such as metal oxides. This combination results in novel materials that overcome some drawbacks of each separated components and enhance the sorption performance. In addition, new trends in hybrid methods combining of water-soluble polymers, membranes, and electrocatalysis/photocatalysis to remove inorganic pollutants have been discussed in this review.